The utilization of Chronic Otitis Media Questionnaire-12 in chronic otitis media with or without cholesteatoma - BİNNETOĞLU, ADEM; BATMAN, ABDULLAH ÇAĞLAR; ŞAHİN, AKIN (SPRINGER, 2020)
Objective This study aimed to compare patients who had chronic otitis media with and without cholesteatoma in terms of the quality of life related to health. Methods The Turkish version of the Chronic Otitis Media Questionnaire-12 (COMQ-12) was completed by totally 100 healthy subjects and 100 patients who had chronic otitis media (COM). The COM group was divided into cholesteatoma and without cholesteatoma [dry tympanic membrane perforation (TMP) and draining ear] groups. Results COMQ-12 score = 3.6 for healthy people. The average scores of dry TMP, draining ear, and cholesteatoma groups were 32.90, 27.34, and 45.95, respectively. A significant difference was between the cholesteatoma and without cholesteatoma groups in total scores (p = 0.001). No difference was found between the groups in age (p = 0.518) and gender (p = 0.975). Conclusion The COMQ-12 could be a useful tool to differentiate chronic otitis media with or without cholesteatoma.
Keywords: Cholesteatoma; Otitis media; Questionnaire; Quality of life; HEARING